The performance of Islamic banks during the 2008 global financial crisis: Evidence from the Gulf Cooperation Council countries. Issue 3 (7th May 2019) - Hussien, Mohammed Ebrahim; Alam, Md. Mahmudul; Murad, Md. Wahid; Wahid, Abu
Abstract : Purpose: The purpose of this study is to analyze the profitability performance of Islamic banks (IBs) of the Gulf Cooperation Council (GCC) region during 2008 global financial crisis. Design/methodology/approach: Bank-specific data are taken from the Bank Scope database and macroeconomic data are collected from International Financial Statistics. Using a panel data series of 30 banks for the period of 2005 to 2011, the study shows the evidence of structural break for the crisis year as well as the factors that impact the profitability of IBs. Findings: The performance of GCC IBs was significantly influenced during the crisis period by capital adequacy, credit risk, financial risk, operational efficiency, liquidity, bank size, gross domestic product, growth rate of money supply, bank sector development and inflation rate. The study also finds that there is a structural change before and after the global financial crisis. Originality/value: This is an original study that shows that the Sharīʿah-compliant banks have performed better during the crisis and are not affected based on their internal performance records; rather, they have been affected indirectly from the macro shock owing to the overall economic crisis.